in Analisis Akuntabilitas Pengelolaan Keuangan Masjid Paripurna di Kecamatan Payung Sekaki Kota Pekanbaru - Rahma, Rahmatika Ritonga (JSE: Jurnal Sharia Economica, 2025)
In Payung Sekaki District there are five plenary mosques, namely the Al-Mujahidin Plenary Mosque which is a plenary mosque for the District level and the Baitussalam Plenary Mosque, Al-Fajar Plenary Mosque, Al-Ikhlas Plenary Mosque, Al-Hidayah Plenary Mosque which is a Plenary Mosque for the village level. With the increasing number of plenary mosques in Pekanbaru City as a center for religious activities and as an example for other mosques, and in line with the vision of the Pekanbaru city government to make Pekanbaru a civil metropolitan city so that in accounting practices and accountability instruments should have been implemented properly. The purpose of this study is to determine the form of Accountability and Transparency and the Application of Accounting as a form of accountability for financial management. This study uses a qualitative research method as the basis for descriptive writing. Data collection techniques use field research, namely interviews, observation and documentation. The results of the study revealed that the Paripurna Mosque in Payung Sekaki District has not been optimal in implementing Accountability and Transparency efforts in financial management, and overall the implementation of accounting at the Paripurna Mosque in Payung Sekaki District has not referred to the applicable financial reporting standards, namely PSAK No. 45.